Are National Cancer Control Indicators for patient experiences being met in regional and remote Australia? A cross-sectional study of cancer survivors who travelled for treatment. Issue 2 (22nd February 2021) - Dunn, Jeff; Goodwin, Belinda; Aitken, Joanne F; March, Sonja; Crawford-Williams, Fiona; Ireland, Michael; Ralph, Nicholas; Zajdlewicz, Leah; Rowe, Arlen; Chambers, Suzanne K
Abstract : Objective: To examine the health services experience of patients with cancer from regional and remote Australia using the Australian National Cancer Control Indicators (NCCI) guidelines as an assessment framework. Design: Cross-sectional. Setting: Queensland non-for-profit cancer accommodation lodges. Participants: Participants were patients with cancer who travelled for treatment from rural and remote Queensland to major urban centres (n=518; age mean=64.6, SD=11.18). Outcome measures: Assessments included NCCI patient indicators, quality of life (QoL), psychological distress and unmet supportive care needs. Results: The frequency at which NCCI indicators were met ranged from 37.5% for receiving an assessment and care plan to 97.3% for understanding explanations about diagnosis. Geographical considerations did not impact patient experience, whereas middle school educated participants were more likely than those with senior-level education or higher to receive an assessment and care plan (OR=1.90, 95% CI 1.23 to 2.91) and to report having their views on treatment taken into account (OR=2.22, 95% CI 1.49 to 3.33). Patients with breast or prostate cancer reported better communication and patient involvement and information and services provision ( r =p<0.001) compared with those with skin and head and neck cancer. When compared with information and service provision, communication and patient involvement showed stronger positive associations with QoL ( z =2.03, p=0.042), psychosocial ( z =2.05, p=0.040) and patient care ( z =2.00, p=0.046) outcomes. Conclusion: The patient care experience varies across the NCCI indicators by sociodemographic and clinical factors that likely reflect healthcare system biases. Perceptions about communication and involvement appear most critical for optimal outcomes and should be a priority action area for cancer control.